PTU-124 Are pseudopolyps the source of tumorigenic mutations in ulcerative colitis?. (28th May 2012) - Jawad, N; Graham, T; Novelli, M; Rodriguez-Justo, M; Feakins, R; Silver, A; Wright, N; McDonald, S
Abstract : Introduction: Pseudopolyps develop as a result of mucosal ulceration and epithelial regeneration. 1 They appear as islands of relatively normal epithelium in otherwise denuded mucosa and are the likely source of epithelium from which the mucosa repairs. They can be associated with areas of dysplasia but are thought to be benign. We have previously shown that protumourigenic mutations can spread through the entire colon in patients with UC-associated cancer. 2 We hypothesise that pseudopolyps are clonal expansions of crypts that have acquired a protumourigenic survival advantage over surrounding normal epithelium that frequently perishes in the inflammatory milieu. Methods: To determine the genetic status of pseudopolyps and frequency of mutated pseudopolyps. DNA extracted from macrodissected UC-associated pseudopolyp tissue sections underwent nested PCR sequencing of common tumour suppressor and oncogenes known to be mutated in colitis associated cancers, using well established published protocols. Results: Of 30 pseudopolyp samples analysed from 30 different patients, four patients had identifiable mutations; in CDKN2A (c.C387T p.129Y), tP53 -exon7 (c.C735T p.245G), and K-RAS (c.G37A p.G13S, and c.G35C p.Gly12Ala). Conclusion: We have shown that pseudopolyps are a potential source of protumourigenic mutations in UC. Pseudopolyps may possibly be the site within the inflamed epithelium where mutations are harboured, and may be the source for restituted bowel. More numbers are needed to be analysed and this is planned for future work and comparison with normal matched tissue is required. These lesions have been traditionally thought to be benign, genetically inert, incidental findings, characteristic of chronic inflammation. Although this data are preliminary, these findings propose an exciting paradigm shift in the way we consider pseudopolyps and may alter endoscopic management of these lesions in the future. Competing interests: None declared. References: 1. Jalan KN, Sircus W, Walker RJ, et al. Pseudopolyposis in ulcerative colitis. Lancet 1969;2 :255. 2. Leedham SJ, Graham TA, Oukrif D, et al. Clonality, founder mutations, and field cancerization in human ulcerative colitis-associated neoplasia. Gastroenterology 2009;136 :542–50.